2021
DOI: 10.1093/bib/bbab249
|View full text |Cite
|
Sign up to set email alerts
|

Published anti-SARS-CoV-2 in vitro hits share common mechanisms of action that synergize with antivirals

Abstract: The global efforts in the past year have led to the discovery of nearly 200 drug repurposing candidates for COVID-19. Gaining more insights into their mechanisms of action could facilitate a better understanding of infection and the development of therapeutics. Leveraging large-scale drug-induced gene expression profiles, we found 36% of the active compounds regulate genes related to cholesterol homeostasis and microtubule cytoskeleton organization. Following bioinformatics analyses revealed that the expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Lomitapide mesylate is an effective microsomal triglyceride transfer protein inhibitor for the treatment of familial hypercholesterolemia. Lomitapide mesylate was first found to exhibit antiviral activity in a drug repurposing candidate screening for COVID-19 (Xing et al, 2021). Our results demonstrated that lomitapide mesylate could inhibit SARS-CoV-2 infection in vivo.…”
Section: Discussionmentioning
confidence: 55%
“…Lomitapide mesylate is an effective microsomal triglyceride transfer protein inhibitor for the treatment of familial hypercholesterolemia. Lomitapide mesylate was first found to exhibit antiviral activity in a drug repurposing candidate screening for COVID-19 (Xing et al, 2021). Our results demonstrated that lomitapide mesylate could inhibit SARS-CoV-2 infection in vivo.…”
Section: Discussionmentioning
confidence: 55%
“…Drug repurposing of SARS-CoV-2 is one of the hottest topics in the applications of the network of SARS-CoV-2. In addition to the aforementioned works, other similar works were done for identifying drug repurposing of SARS-CoV-2. ,, …”
Section: Methods and Approachesmentioning
confidence: 99%
“…In the study, it was found to change the expression of mRNA levels of HMGCS1 (3-hydroxy-3-methylglutaryl-CoA synthase 1) in human lung primary small airway cells by 3–8-fold at 0.5 μM concentration. The anti- SARS-CoV-2 efficacy of monensin (EC 50 ) was predicted to be 11 μM in Vero E6 cells …”
Section: Potential Glycosylation Inhibitors For Sars-cov-2mentioning
confidence: 99%
“…The anti-SARS-CoV-2 efficacy of monensin (EC 50 ) was predicted to be 11 μM in Vero E6 cells. 34 5.1.3. Mannostatin A.…”
Section: Tunicamycin Tunicamycin Is An Antibiotic Produced Bymentioning
confidence: 99%